Advances in mechanism and regulation of PANoptosis: Prospects in disease treatment - Zhu, Peng; Ke, Zhuo-Ran; Chen, Jing-Xian; Li, Shi-Jin; Ma, Tian-Liang; Fan, Xiao-Lei (Frontiers in Immunology, 2023)
PANoptosis is a new research hotspot at the moment, and it is a cell death mode in which pyroptosis, apoptosis, and necroptosis all occur in the same cell population. Essentially, PANoptosis is a highly coordinated and dynamically balanced programmed inflammatory cell death pathway, which combines the main features of pyroptosis, apoptosis, and necroptosis. Many variables, such as infection, injury, or self-defect, may be involved in the occurrence of PANoptosis, with the assembly and activation of the PANoptosome being the most critical. PANoptosis has been linked to the development of multiple systemic diseases in the human body, including infectious diseases, cancer, neurodegenerative diseases, and inflammatory diseases. Therefore, it is necessary to clarify the occurrence process, the regulation mechanism of PANoptosis, and its relationship to diseases. In this paper, we summarized the differences and relations between PANoptosis and three kinds of programmed cell death, and emphatically expounded the inducing factors, molecular mechanism, and regulation mode of PANoptosis, expecting to promote the application of PANoptosis regulation in disease treatment.